When is organisational resizing helpful or harmful for innovation outputs? - Boumediene Ramdani (14158881) (2024)
Research on the effect of changing staffing levels (i.e. resizing) on organisational innovation has generated mixed and often contradictory results. Recent research has attempted to reconcile such inconsistencies by showing that this effect on innovation depends on the firm’s staffing level prior to downsizing. Since firms seek to downsize as well as upsize their staffing levels, the effect of resizing (downsizing and upsizing) on innovation and the magnitude of such effect is still unknown. Using a longitudinal dataset of UK firms, we examine the effect of resizing on innovation outputs and its magnitude in resource-rich and resource-constrained firms. Our results suggest that upsizing in resource-constrained firms and downsizing in resource-rich firms is helpful for innovation, whereas upsizing in resource-rich and downsizing in resource-constrained firms have the reverse effect. Compared with resource-rich firms, the effect of resizing on innovation outputs is more pronounced in resource-constrained firms. These results have several practical managerial implications. Other Information Published in: Research in International Business and Finance License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ribaf.2024.102503